A field-grown transgenic tomato line expressing higher levels of polyamines reveals legume cover crop mulch-specific perturbations in fruit phenotype at the levels of metabolite profiles, gene expression, and agronomic characteristics. - Neelam, A; Cassol, T; Mehta, R; Abdul-Baki, A; Sobolev, A; Goyal, R; Abbott, J; Segre, A; Handa, A; Mattoo, A (2008)
Genetic modification of crop plants to introduce desirable traits such as nutritional enhancement, disease and pest resistance, and enhanced crop productivity is increasingly seen as a promising technology for sustainable agriculture and boosting food production in the world. Independently, cultural practices that utilize alternative agriculture strategies including organic cultivation subscribe to sustainable agriculture by limiting chemical usage and reduced tillage. How the two together affect fruit metabolism or plant growth in the field or whether they are compatible has not yet been tested. Fruit-specific yeast S-adenosylmethionine decarboxylase (ySAMdc) line 579HO, and a control line 556AZ were grown in leguminous hairy vetch (Vicia villosa Roth) (HV) mulch and conventional black polyethylene (BP) mulch, and their fruit analysed. Significant genotypexmulch-dependent interactions on fruit phenotype were exemplified by differential profiles of 20 fruit metabolites such as amino acids, sugars, and organic acids. Expression patterns of the ySAMdc transgene, and tomato SAMdc, E8, PEPC, and ICDHc genes were compared between the two lines as a function of growth on either BP or HV mulch. HV mulch significantly stimulated the accumulation of asparagine, glutamate, glutamine, choline, and citrate concomitant with a decrease in glucose in the 556AZ fruits during ripening as compared to BP. It enables a metabolic system in tomato somewhat akin to the one in higher polyamine-accumulating transgenic fruit that have higher phytonutrient content. Finally, synergism was found between HV mulch and transgenic tomato in up-regulating N:C indicator genes PEPC and ICDHc in the fruit.